Radiotherapy as a Conservative Treatment for Breast Cancer - von Pfuhl, Oscar Rocha (2023)
The review of 545 cases of cancer of the breast, 10% of which were treated by exclusive radiotherapy, emphasized the trend towards conservative treatment, because 29,8% of mastectomized women died within two years from the operation with distant metastases. As it is possible with radiotherapy to cause fibrosis or keep inactive breast tumors up to 5 cm diameter for two years or longer, one must consider irradiation as a good option for young women with small tumors. It was used a combination of tangencial radiotherapy up to 5.000 rads to the whole breast with a boost dose two weeks later of 3.000 to 4.000 rads by means of intersticial radiotherapy given only to the palpable tumor.This was fulfilled by the afterloading method according to a System described as geometrization of the breast by parallel plates where holes were drilled for the needies. No recurrence was seen in 4 years in the selected group of 12 patients submitted to the mentioned treatment.